2018
DOI: 10.1007/s10393-018-1335-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Rodent-Borne Viral Zoonoses in Trento, Italy

Abstract: Rodent-borne hanta- and arenaviruses are an emerging public health threat in Europe; however, their circulation in human populations is usually underestimated since most infections are asymptomatic. Compared to other European countries, Italy is considered 'low risk' for these viruses, yet in the Province of Trento, two pathogenic hantaviruses (Puumala and Dobrava-Belgrade virus) and one arenavirus (Lymphocytic Choriomeningitis Virus) are known to circulate in rodent reservoirs. In this paper, we performed a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…There are very few recently published serological surveys of LCMV infection. In this study, the overall seroprevalence rate was 6.8% which is similar to the seropositivity in an Iraqi study conducted in 2012–2013 (6.4%) [ 20 ] and an Italian study conducted in 2015 (7%) [ 29 ]. In the 1990s, several studies were conducted in the Americas.…”
Section: Discussionsupporting
confidence: 83%
“…There are very few recently published serological surveys of LCMV infection. In this study, the overall seroprevalence rate was 6.8% which is similar to the seropositivity in an Iraqi study conducted in 2012–2013 (6.4%) [ 20 ] and an Italian study conducted in 2015 (7%) [ 29 ]. In the 1990s, several studies were conducted in the Americas.…”
Section: Discussionsupporting
confidence: 83%
“…Local abiotic factors (e.g., temperature, moisture, protection from UV light) may also affect the epidemiological characteristics of PUUV and the number of NE cases, and of PUUV transmission in particular, by influencing bank vole abundance and viral persistence outside the host [ 11 , 63 , 64 , 65 ]. Ecological niche modeling has been used to predict the distribution of NE cases in Europe [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased epidemiological vigilance may provide some answers. In any event, it would appear to be warranted: it has been recently reported that the seroprevalence of antibodies against LCMV in the Province of Trento (Italy) has been increasing over time [34].…”
Section: Discussionmentioning
confidence: 99%